Analisis Kegagalan Mediasi dalam Perkara Perceraian di Pengadilan Agama Merauke - Sarko; Faisal; Ade Yamin (SAKINAH: Jurnal Hukum Keluarga Islam, 2025)
Mediation is an effort to resolve divorce cases through negotiations assisted by a third party called a mediator. As an alternative dispute resolution, it turns out that in its implementation, many obstacles and hurdles must be overcome to achieve success in mediation. This research aims to reveal the reality of the above problems by explaining how the mediation process is carried out at the Merauke Religious Court, the factors inhibiting mediation failure, and the implications of failure in the mediation process at the Merauke Religious Court. The method used in this thesis is to prioritize a qualitative approach. From the results of the research carried out, it was revealed that the implementation of mediation in the Merauke religious courts refers to regulation number 1 of 2016 concerning procedures for implementing mediation in religious courts, with a series of stages in the form of a mediation process and resolving cases by agreeing. In its implementation, there are obstacles faced by mediators that cause failure in mediation, while the factors referred to are internal factors which are prolonged conflicts within the household as well as a strong desire to separate, and external factors in the form of less than optimal mediation implementation times and There are also third parties who influence the mediation process. As an implication, this thesis shows that the existence of these obstacles has implications for the psychology of the parties to the dispute and the performance of the Merauke religious court itself. Keywords: Divorce, Madiation Failure, Religion Rourt     Abstrak: Mediasi merupakan salah satu upaya dalam menyelesaikan perkara perceraian melalui perundingan yang dibantu pihak ketiga yang disebut sebagai mediator. Sebagai alternatif penyelesaian sengketa, ternyata dalam pelaksanaannya masih mendapatkan banyak hambatan dan rintangan yang harus dilalui untuk mencapai keberhasilan dari mediasi. Penelitian ini bertujuan untuk mengungkapkan realitas permasalahan di atas dengan menjelaskan bagaimana proses mediasi yang dilakukan di Pengadilan Agama Merauke, faktor penghambat kegagalan mediasi dan implikasi dari adanya kegagalan dalam proses mediasi di Pengadilan Agama Merauke. Metode yang digunakan dalam penelitian ini adalah mengedepankan pendekatan kualitatif. Dari hasil penelitian yang dilakukan terungkap bahwa pelaksanaan mediasi di Pengadilan Agama Merauke merujuk pada Perma Nomor 1 Tahun 2016 tentang prosedur pelaksanaan mediasi di Pengadilan Agama, dengan rangkaian tahapannya berupa proses mediasi dan penyelesaian perkara dengan membuat kesepakatan. Dalam pelaksanaannya terdapat hambatan-hambatan yang dihadapi oleh mediator sehingga menjadi penyebab kegagalan dalam mediasi, adapun faktor yang dimaksud berupa faktor internal yang merupakan konflik yang berkepanjangan di dalam rumah tangga serta keinginan yang kuat untuk berpisah dan faktor eksternal berupa waktu pelaksanaan mediasi yang kurang maksimal dan juga ada pihak ketiga yang mempengaruhi proses mediasi. Sebagai implikasi, penelitian ini menunjukkan dengan adanya hambatan-hambatan tersebut berimplikasi terhadap psikologi pihak yang bersengketa dan kinerja dari Pengadilan Agama Merauke itu sendiri.